A view from the head end medical cartoons to ease the pain - Yentis, S. M. (Steven M.) (tfm Publishing, 2005)
Choosing an easy life as an anaesthetist over the cut and thrust of art college, the author has been drawing medical cartoons, whilst waiting for surgeons to turn up or his regional blocks to work. This collection of drawings represents a wry look at life in the operating theatre, wards and clinic, as seen from the Head End.